Nutrient requirements of exotic tree species in Zimbabwe - Sanginga, N.; Gwaze, D.; Swift, M.J. (1991)
Pot and field experiments were conducted in the greenhouse and at three field sites (Marondera, Domboshawa and Makoholi) in Zimbabwe to examine the effects of soils and fertilizers on nutrient uptake and growth of 6 exotic tree species (Eucalyptus camaldulensis, E. grandis, E. tereticornis, Leucaena leucocephala, Casuarina cunninghamiana, and Acacia holosericea). Plant growth, N and P contents of all species were increased by the application of N, P, K and micronutrient fertilizers. The effect of individual nutrients (N, P, K and micronutrients) and their combination on Eucalyptus species was further investigated in a pot experiment using soil from Domboshawa. Eucalyptus species responded only to N application and no significant interactions were found between N and the other elements. Nutrient uptake results showed that E. camaldulensis and E. tereticornis removed more cations than the N-fixing trees but only in the fertilized treatments. L. leucocephala and C. cunninghamiana were higher in P, but no clear trends were observed for N. Plant growth and nutrient uptake by E. camaldulensis. C. cunninghamiana and A. holosericea were assessed in the field at the three sites. Plant species grown in the Marondera site had greater height and diameter at breast height (DBH) than those in the two other sites. These results followed trends in soil nutrient contents. The analysis of foliage revealed differences in the nutrient concentration of leaves from different trees, but no effect of site was found. The interrelationships between plant characteristics, soil and foliage nutrients were examined. In a pot experiment, mineral N was the only variable correlated with growth response and nutrient uptake, while in the field the only significant correlation was obtained with soil pH.